2018
DOI: 10.1186/s12998-018-0184-0
|View full text |Cite
|
Sign up to set email alerts
|

Can chiropractors contribute to work disability prevention through sickness absence management for musculoskeletal disorders? - a comparative qualitative case study in the Scandinavian context

Abstract: BackgroundDespite extensive publication of clinical guidelines on how to manage musculoskeletal pain and back pain in particular, these efforts have not significantly translated into decreases in work disability due to musculoskeletal pain. Previous studies have indicated a potential for better outcomes by formalized, early referral to allied healthcare providers familiar with occupational health issues. Instances where allied healthcare providers of comparable professional characteristics, but with differing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Allied health professionals responsible for injured workers’ care such as physiotherapists and chiropractors have also developed and published position papers and best practices articles to help improve care for injured workers [812]. Increased attention towards factors that could facilitate or hinder the care of injured workers has also been noted [1315]. …”
Section: Introductionmentioning
confidence: 99%
“…Allied health professionals responsible for injured workers’ care such as physiotherapists and chiropractors have also developed and published position papers and best practices articles to help improve care for injured workers [812]. Increased attention towards factors that could facilitate or hinder the care of injured workers has also been noted [1315]. …”
Section: Introductionmentioning
confidence: 99%
“…Papers in this series have again revealed deeply rooted disagreements within the chiropractic profession about what chiropractic is, and what it should be, as a profession [13,19,20], as well as disagreements and variation in relation to education of chiropractors [14,15] and chiropractic clinical practice [11]. In our opinion, it is ironic that while chiropractic has a strong presence in large parts of the world [3], is taking on increasingly important roles in disability prevention [6,7,17], in the military [5] and in interprofessional care [8] as well as growing research capacity [16], discussions about fundamental values and direction of the profession are unresolved. This unresolved issue creates confusion for stakeholders and threatens to impede professionalization and cultural authority.…”
Section: Discussionmentioning
confidence: 95%
“…disability prevention both informally and as part of system-supported pathways [6,7]. Another example of chiropractors functioning in interprofessional collaboration was provided by Wirth et al who reported on outcomes and trajectories of patients referred from a surgical department to chiropractic care [8].…”
Section: Commentarymentioning
confidence: 99%
“…This paper presents a cross-sectional, population-based survey, which is the second phase of a two-phased sequential, exploratory mixed-methods study. The first phase of the study involved a qualitative case study [14]. The interviews reported in the qualitative phase identified perceived barriers and facilitators, as well as practice behaviours of a group of musculoskeletal practitioners (chiropractors) with regards to sickness absence management (SAM) of their patients.…”
Section: Introductionmentioning
confidence: 99%
“…But, the most noticeable difference is that since 2008, the Norwegian chiropractors have been licensed to certify sickness absence up to 12 weeks. A full overview of the differences is provided elsewhere [14].…”
Section: Introductionmentioning
confidence: 99%